2010
DOI: 10.1086/651136
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Suppression of Minority Drug‐Resistant HIV Type 1 (HIV‐1) Variants Present at Primary HIV‐1 Infection by Ritonavir‐Boosted Protease Inhibitor–Containing Antiretroviral Therapy

Abstract: Minority variants, in particular viruses harboring the M184V mutation, were efficiently suppressed in patients with acute infection who received a ritonavir-boosted PI and 2 NRTIs (most regimens included lamivudine). Under this high genetic resistance barrier regimen, the M184V was not further selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…These studies show that minority M184V carrying HIV-1 variants are more frequently detectable than minority K103N carrying HIV-1 variants. 15,20,25,30 We and others have previously shown that the detection of minority NNRTI-resistant HIV-1 variants prior to ART can be associated with an increased risk for virological failure in patients receiving regimens containing an NNRTI. 14,16,17,[31][32][33] Although in the present study a total of 65 patients (44.5%) were treated with an NNRTI-containing regimen, only 2 of the 8 patients who harbored the K103N mutation at low frequencies received an NNRTI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies show that minority M184V carrying HIV-1 variants are more frequently detectable than minority K103N carrying HIV-1 variants. 15,20,25,30 We and others have previously shown that the detection of minority NNRTI-resistant HIV-1 variants prior to ART can be associated with an increased risk for virological failure in patients receiving regimens containing an NNRTI. 14,16,17,[31][32][33] Although in the present study a total of 65 patients (44.5%) were treated with an NNRTI-containing regimen, only 2 of the 8 patients who harbored the K103N mutation at low frequencies received an NNRTI.…”
Section: Discussionmentioning
confidence: 99%
“…in treatment-naïve patients, where a correlation between NRTIor NNRTI resistance mutations at low frequencies and virological failure was not observed in patients receiving PIs. 15,17,20 In summary, although there is some evidence that pre-existing NNRTI resistance mutations at low frequencies can compromise the success of NNRTI-containing ART regimens, the importance of drug-resistant minorities for the outcome of ART is still a matter of controversy. This is a highly complex issue and multiple factors have to be considered, for instance, absolute copy numbers of the minority drug-resistant HIV-1 variants (mutational load), possible linkage of drug resistance mutations, and genetic barriers to resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using more-sensitive genotypic assays, different research groups (15,30,32,37,48,58,65) have reported higher proportions of transmitted DRM in ART-naive individuals. The clinical importance of these low-level DRM remains unclear, as they have been associated with clinical consequences in some (21,24,32,36,37,40,46,54,55,63,66,71) but not all (30,47,58) studies.…”
mentioning
confidence: 99%